Healing by a Mere Touch as a Christian Concept - Lalleman, Pieter J. (Tyndale bulletin, 1997)
On the basis of Otto Weinreich’s Antike Heilungswunder (1909), it is generally thought that the idea that a simple touch can have healing power originated with the Greeks. The present essay argues, however, that this concept is proper to the Gospels and to texts dependent on them. There are no Greek cases of such healings before the rise of Christianity. Before Christ, the concept of healing by a mere touch occurs only in one isolated case, viz. the Genesis Apocryphon from Qumran.